Ecuacin de la circunferencia, aplicacin prctica - Vigo Romero, Jesus Jobita (2018)
The purpose of this learning session is for students to identify the equation of the circumference from the points of coordinates in the Cartesian plane and vice versa through problem solving, discovering the pertinent and adequate strategies to be applied in the solution of the proposed problems, bearing in mind the previous knowledge for the consolidation of the new knowledge. The first chapter is destined to the demonstration of strategies of the Learning Session called "The Circumference Equation. Practical application", considering in its construction the pedagogical and didactic processes of the area of mathematics. In the second chapter the foundation of the Mathematics area is exposed, according to the DCN 2015 and the Routes of Learning 2015; the Theoretical Support taking into account the procedures and strategies to be used to determine the equation of the circumference from the values known as the center and the radius, bearing in mind the previous knowledge as the distance between two points and the square of the addition/subtraction of a binomial. The third chapter presents the Pedagogical Support referred to the psycho pedagogical principles, pedagogical processes in the methodological process, means and materials, as well as the procedures and instruments of evaluation.